Synthesis and studies on the mGluR agonist activity of FAP4 stereoisomers. Issue 12 (15th June 2015) - Ivashkin, Pavel; Lemonnier, Gérald; Tora, Amélie S.; Pin, Jean-Philippe; Goudet, Cyril; Jubault, Philippe; Pannecoucke, Xavier
Graphical abstract: Abstract: The four stereoisomers of 1-amino-2-fluoro-2-(phosphonomethyl)cyclopropane-1-carboxylic acid (FAP4) were synthesized via diastereoselective Rh(II)-catalysed cyclopropanation of a phosphonylated fluoroalkene. Different isomers of FAP4 and the corresponding non-fluorinated analogs showed a similar pharmacological profile against the isoforms of metabotropic glutamate receptor (mGluR). Within the fluorinated series, (−)-( Z )-FAP4 and (−)-( E )-FAP4 demonstrated the highest agonist activity against mGlu4 (EC50 0.10 μM). Our results suggest that fluorocyclopropanes bearing an amino-acid function can be suitable for the development of potent conformationally restricted mGluR agonists.